A powerful Numeric-analytic Technique for handling prey-predator problems - Chowdhury, Md. Sazzad Hossien (2012)

(untitled)
In this paper, a new reliable algorithm based on an adaptation of the standard Adomian decomposition method (ADM) is presented. The ADM is treated, as an algorithm in a sequence of intervals (i.e. time step) for finding accurate approximate solutions to the famous prey-predator problem. The numerical results obtained from the new algorithm of ADM and the classical fourth-order Rungge-Kutta (RK4) methods are in complete agreement.